A hospital based clinico-pathological study of soft tissue tumors - R.V., Bhosle; Sreenivasa, P. (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2018)
Background: Soft tissue sarcomas can develop from soft tissues like fat, muscle, nerves, fibrous tissues, blood vessels, or deep skin tissues. They can be found in any part of the body, commonly seen in the trunk, head and neck area, internal organs, and the area in back of the abdominal cavity (known as the retroperitoneum). Most of them develop in the arms or legs. Aim: The study was conducted to know the incidence, location of soft tissue tumors at different age group individuals and to analyze the various types and subtypes of soft tissue tumors. Materials & Methods: Total of 124 cases of soft tissue lesions were analyzed retrospectively and prospectively in a period of 1.5 years. The prospective study was conducted in the department of surgery and Institutional ethical committee approval was obtained. A detailed clinical data was collected by using the standard data sheet and biopsy specimens were sent to pathology department for histopathological evaluation. Results: The present clinicopathological study included 124 soft tissue tumor cases in different age groups. The occurrence of age wise soft tissue tumors has been depicted in table 1. Out of 124 soft tissue tumors, 97 were benign type, 27 were malignant variety. Conclusion: The present hospital-based study reports data of various types of benign and malignant soft tissue tumors, their relative incidence in male and female and their distribution with respect to the anatomical location of human body. Benign tumors required simple excision, but aggressive benign myxoid tumors and malignant soft tissue tumors require wide surgical excision and close follow up.